226k views
0 votes
-7p+2(5p-8)=6(p+6)-7

2 Answers

4 votes
P=5

-7p+2(5p-8)=6(p+6)-7
Distribute
-7p+10p-16=6p+36-7
Add -7p and 10p together
3p-16=6p+36-7
Subtract 7 from 36
3p-16=6p+29
+6p (on both sides)
9p-16=29
+16 (on both sides)
9p=45
Divide both sides by 9
P=5
User Krishna Agarwal
by
4.9k points
2 votes

Answer:

-15

Explanation:

-7p+10p-16=6p+36-7

3p-16=6p+29

3p-6p=29+16

-3p=45

p=45/-3

p=-15

User BADAOUI Mohamed
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.